Monty Python live! Vol. II [videorecording (DVD)] - Chapman, Graham, 1941-1989; Cleese, John; Palin, Michael; Gilliam, Terry; Idle, Eric; Jones, Terry, 1942-2020- (A & E : Distributed by New Video, 2001)
Parrot sketch not included is a 20-year anniversary celebration of the best of Monty Python; Monty Python's german episode #1 includes German versions of The Lumberjack song and Colin "Bomber" Harris self-wrestling recorded for German and Austrian television.